2020
DOI: 10.1002/ange.202012544
|View full text |Cite
|
Sign up to set email alerts
|

Sugar‐Based Polymers from d‐Xylose: Living Cascade Polymerization, Tunable Degradation, and Small Molecule Release

Abstract: Enyne monomers derived from D‐xylose underwent living cascade polymerizations to prepare new polymers with a ring‐opened sugar and degradable linkage incorporated into every repeat unit of the backbone. Polymerizations were well‐controlled and had living character, which enabled the preparation of high molecular weight polymers with narrow molecular weight dispersity values and a block copolymer. By tuning the type of acid‐sensitive linkage (hemi‐aminal ether, acetal, or ether functional groups), we could chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Previously, we demonstrated that our sugar-based polymers with acetal or hemi-aminal ether linkages (contained in every repeat unit) could be fully degraded under mild acidic conditions to well-defined small molecules. 13,14 As complete repeat units in P1 and P2 also contain 2,5-dihydrofuran moieties, they could be cleaved under dilute HCl conditions to generate furan moieties (Figure 4), which provided easily identifiable downfield signals in the 1 H NMR spectrum. On the other hand, the interrupted repeat unit linkages were stable under the degradation conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previously, we demonstrated that our sugar-based polymers with acetal or hemi-aminal ether linkages (contained in every repeat unit) could be fully degraded under mild acidic conditions to well-defined small molecules. 13,14 As complete repeat units in P1 and P2 also contain 2,5-dihydrofuran moieties, they could be cleaved under dilute HCl conditions to generate furan moieties (Figure 4), which provided easily identifiable downfield signals in the 1 H NMR spectrum. On the other hand, the interrupted repeat unit linkages were stable under the degradation conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…10−12 Recently, we successfully polymerized new enyne monomers (2) derived from sugars (glucose, galactose, or xylose). 13,14 Substituents on the dihydro-2H-pyran core of the monomers, and their stereochemistry, had an appreciable influence on the cascade polymerization performance. For instance, having an anti-relationship between the substituents on the ring enabled faster and better controlled polymerization.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations